2019
DOI: 10.1097/psy.0000000000000675
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Training and Physical Health: Mechanisms and Outcomes

Abstract: Objective: There has been substantial research and public interest in mindfulness interventions, biological pathways, and health over the past two decades. This article reviews recent developments in understanding relationships between mindfulness interventions and physical health. Methods: A selective review was conducted with the goal of synthesizing conceptual and empirical relationships between mindfulness interventions and physical health outcomes. Results: Initial randomized controlled trials (RCTs) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 90 publications
1
109
0
1
Order By: Relevance
“… 33 Several valuable models describe potential psychological and neurobiological mechanisms through which MM could exert its salutary effects. 30 , 36 45 …”
Section: Mindfulness and Mbismentioning
confidence: 99%
“… 33 Several valuable models describe potential psychological and neurobiological mechanisms through which MM could exert its salutary effects. 30 , 36 45 …”
Section: Mindfulness and Mbismentioning
confidence: 99%
“…Body Scan/ Bodily Awareness-a subtype of distraction in form of bodily sensations-can lead to a reduction in fear-avoidance behavior and an improved perception of sensory information [44], while increasing neuronal activity and concentration of neurotransmitter [45]. Furthermore, body scans-mostly integrated in a mindfulness-based stress reduction program (MBSR [46])-may support the restructuring of the brain volume and biochemical deteriorations that affect pain patients [47]. As it was shown that MBSR is powerful in increasing stress resilience [48], this association may additionally reinforce the intended pathways through the combination of exercise and distraction [49].…”
Section: Rationale Of Selectionmentioning
confidence: 99%
“…An overarching goal of MBCT is to enable participants to relate to their own thoughts, emotions and bodily sensations with mindful awareness, and thereby break the habitual dysfunctional cycle of rumination, maladaptive emotion regulation and self-criticism that make them vulnerable for depressive relapse. There are different conceptualizations of mindfulness in the research literature, but there is general agreement that mindfulness encompasses self-regulation of attention to monitor present-moment experience, and the concurrent attitudinal qualities of acceptance, openness and non-judgment [34,35]. In mindfulness-based interventions, participants learn an alternative to elaborating on one's current state by way of negative repetitive thinking, or deficient coping by way of avoidance and passivity.…”
Section: Introductionmentioning
confidence: 99%